Comparative Evaluation of Contrast-enhanced Ultrasound and Indocyanine Green Lymphography for Lymphatic Mapping: A Retrospective Study - Samyd S. Bustos, MD; Maria Rios, MPH; Samuel Jang, MD; Gina K. Hesley, MD; Christine U. Lee, MD, PhD; Nho V. Tran, MD; Vahe Fahradyan, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Lymphaticovenous anastomosis (LVA) is an effective surgical treatment for extremity lymphedema. Indocyanine green (ICG) fluorescent lymphography, the traditional standard for imaging lymphatic vessels, has limitations, including difficulty depicting deeper or congested lymphatics and contraindication in iodine hypersensitivity. This study evaluated contrast-enhanced ultrasound (CEUS) with microbubbles for identifying lymphatic vessels for LVA and compared it with ICG lymphography. Methods:. In this single-center retrospective review, intraoperative CEUS with intradermal injection of microbubble suspension (Lumason, Bracco Diagnostics, Inc.) was used in patients before LVA surgery between October 2019 and February 2023. Pre- or intraoperative ICG lymphography was also used to identify target lymphatic vessels. All patients diagnosed with primary or secondary extremity lymphedema who underwent LVA were included. Technical success rate was defined as lymphatic vessels identified by CEUS that led to successful LVAs. Descriptive statistics were used. Results:. Thirty-two patients underwent LVA surgery, with a mean age of 58.5 ± 13.9 years. CEUS identified lymphatic vessels in all 32 patients, including 7 in whom ICG failed. Two patients with ICG allergy underwent CEUS only. CEUS identified more candidate lymphatics per patient (5.3 ± 4.2) compared with ICG (2.5 ± 2.7). Of the 182 anastomoses, 96 (52.8%) were identified by both CEUS and ICG, 75 (41.2%) by CEUS only, and 11 (6%) by ICG only. Conclusions:. CEUS is a promising tool for identifying lymphatic vessels in patients with lymphedema undergoing LVA, particularly when ICG lymphography is inadequate or contraindicated.